Bone healing around titanium implants in two rat colitis models - Kuchler, Ulrike; Luvizuto, Eloa R. [UNESP]; Muñoz, Fernando; Hofbauer, Julia; Watzek, Georg; Gruber, Reinhard (Wiley, 2013)
Objective: Crohn's disease is a chronic inflammatory process that has recently been associated with a higher risk of early implant failure. Herein we provide information on the impact of colitis on peri-implant bone formation using preclinical models of chemically induced colitis. Methods: Colitis was induced by intrarectal instillation of 2,4,6-trinitro-benzene-sulfonic-acid (TNBS). Colitis was also induced by feeding rats dextran-sodium-sulfate (DSS) in drinking water. One week after disease induction, titanium miniscrews were inserted into the tibia. Four weeks after implantation, peri-implant bone volume per tissue volume (BV/TV) and bone-to-implant contacts (BIC) were determined by histomorphometric analysis. Results: Cortical histomorphometric parameters were similar in the control (n = 10), DSS (n = 10) and TNBS (n = 8) groups. Cortical BV/TV was 92.2 ± 3.7%, 92.0 ± 3.0% and 92.6 ± 2.7%. Cortical BIC was 81.3 ± 8.8%, 83.2 ± 8.4% and 84.0 ± 7.0%, respectively. No significant differences were observed when comparing the medullary BV/TV and BIC (19.5 ± 6.4%, 16.2 ± 5.6% and 15.4 ± 9.0%) and (48.8 ± 12.9%, 49.2 ± 6.2 and 41.9 ± 11.7%), respectively. Successful induction of colitis was confirmed by loss of body weight and colon morphology. Conclusions: The results suggest bone regeneration around implants is not impaired in chemically induced colitis models. Considering that Crohn's disease can affect any part of the gastrointestinal tract including the mouth, our model only partially reflects the clinical situation. © 2012 John Wiley & Sons A/S.
Keywords: Bone healing around implants; Bone regeneration; Colitis; Dental implants; Morbus Crohn; Rat